Adaptasi Pelaku Bisnis Besi Tua Suku Bangsa Madura Terhadap Persaingan Bisnis Besi Tua di Kota Surabaya - Aftina Fityan Sholeh (Biokultur, 2020)
Adaptation to the scrap metal business in Surabaya as a livelihood is monitored and analyzed the Madurese adaptation behavior in the scrap metal business operating in the City of Surabaya. This study uses ethnographic methods with data collection techniques of observation and in-depth interviews, data analysis techniques using ethnographic analysis using the Adaptation Theory of Usman Pelly. The results showed that in the adaptation carried out by scrap metal business (Founders) as immigrants of the Madurese Tribe in the City of Surabaya by working with fellow relatives of the scrap metal businessmen of the Madurese Tribe in the City of Surabaya, in addition, relatives who had first migrated in the City Surabaya can guarantee the economic life of overseas relatives by creating jobs within the scope of the scrap metal business. This was repeated to other relatives who wanted to develop in overseas lands as a reciprocal relationship as an Adaptation process. This adaptation was carried out in the process of dealing with the competition of the scrap metal business which strengthened the dominance of the Madurese Tribe in the scrap metal business in the city of Surabaya